Adaptation and Innovation Strategies in Facing Business Challenges: A Case Study in the Digital Industry - Khuan, Hendri; Yogi Sugiarto Maulana; Triwijayati, Anna; Hana Rengganawati; Zainal Arifin (Eastasouth Institute, 2023)
The digital industry has witnessed rapid growth, powered by innovative start-ups that drive change and transformation. In the bustling digital landscape of Bandung City, these start-ups face a multitude of challenges ranging from market uncertainties to resource limitations. This qualitative study explores how digital start-ups in Bandung City navigate these challenges through adaptation and innovation strategies. Through in-depth interviews and thematic analysis, this research sheds light on the dynamic strategies that enable these start-ups to thrive and remain competitive in the ever-evolving digital ecosystem. The findings offer practical insights for founders and decision-makers while enriching the theoretical understanding of adaptation and innovation within a localized context.